Comparison of efficacy of post operative analgesic regimes for post operative pain control in adults with long bone fractures - a cross-sectional study in Hospital Tengku Ampuan Afzan Kuantan - Mohd Ariff Razani bin Abd Razak (Kulliyyah of Medicine, International Islamic University Malaysia, 2015)
This is a cross-sectional study of 79 patients with a single long bone fracture treated with open reduction and internal fixation in Hospital Tengku Ampuan Afzan, Kuantan (HTAA). The aim of this study is to compare the post-operative pain relief achieved using different analgesic groups. The efficacy of the post operative pain regimes used in the management of acute post-operative pain in HTAA was evaluated. Recruitment of patients was performed from June to October 2014, according to the inclusion and exclusion criteria. The sample population was randomized by admission into three arms, with a calculated minimum of 23 patients for each (Parecoxib = 27, Tramadol = 26, Diclofenac sodium = 26). All patients were administered a local anaesthetic (LA = Ropivacaine 0.2%, 10 mls) after surgical wound closure. The three groups were then given intramuscular (IM) injections of Diclofenac sodium (Voltaren), Tramadol hydrochloride (Tramal), and Parecoxib (Dynastat) at the recommended standard dosages, up to 72 hours after surgery, or before discharge. The main outcome is the measurement of the pain score, along with any detrimental effects to the patient commonly associated with the usage of the analgesics used. The primary tool for assessment used in this study was the validated Acute Pain Service (APS) form used by the Department of Anesthesia in HTAA. This study showed a reduction in pain scores between all groups of analgesics over time, with no obvious difference between the three arms. However male patients exhibited lower initial pain scores as compared to their female counterparts, who have a higher perception to pain. Tramadol was found to produce the most significant post-operative pain relief in the female group of patients in all the three arms studied, even after observed over time. Although achieving adequate pain relief from all groups, no significant difference in efficacy was found for the males in any of the arms studied. All sampled patients achieved adequate pain relief and pain scores, without significant adverse events. No difference in overall outcome was observed between all groups of analgesics. Significant differences of outcomes were also not seen between the ethnic groups. Females had a better response to Tramadol overall even over time, whereas males exhibited similar outcomes across all three groups. Although initial pain scores were higher in females, no significant statistical difference was observed in the reduction of pain scores over time. A larger sample size, particularly female subjects, would better exhibit a significant effect size.